A utilização de extractos de origem vegetal na inibição do crescimento fúngico - Mexia, António (2003)
We are seeing actually a growing concern and awareness by the public opinion related to the utilization of pesticides and to the presence of their residues in foodstuff. These facts lead the scientific organisations to search for new forms of foodstuff protection against the microorganism’s contamination. The active compounds, biologically produced by plants are an example of substances considered safe. These plant extracts have a better acceptance by the public opinion and are less harmful to health than the synthetic ones. In this work, we have selected aqueous extracts of cinnamon (Cinnamomum verum J. Presl), coriander (Coriandrum sativum L.), peppermint (Mentha piperita L.), chamomile (Anthemis nobilis L.), malva (Malva sylvestris L.) and parsley (Petroselinum crispum Mill.) with the objective of study their inhibitory effect and fungistatic power on fungi development. We hope to make a contribution to the overall work that has been done in the field of investigation of new active substances with fungistatic capabilities, that can be used as a substitute of pesticides.